Mixed signals - Borison, B. K. (Lovelight, 2023)
"A small-town baker learns to raise her expectations for love with some help from a handsome local teacher in this sunny romantic comedy. Layla Dupree has given up on love. She's waded through all the fish in the sea, each one more disappointing than the last. Apparently, owning the bakery at Inglewild's most romantic destination does not help one's love life-despite Layla's best efforts. All she wants is a partner who gives her butterflies, not someone who ghosts her at dinner and leaves her with the check. Good thing Caleb Alvarez has the perfect solution. After saving Layla from another date gone bad, he has a simple proposition: one month of no-strings dating. He'll do his best to renew her faith in men while she rates his romantic game. It's a win-win situation. All the benefits of dating without the added pressure of feelings and unmet expectations. But there's one ingredient they haven't considered. The chemistry between them is red-hot, and the urge to take things to the next level is more tempting than Layla's mocha fudge brownies"--